2020
DOI: 10.18632/aging.104138
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy in patients with COVID-19: a systematic review and meta-analysis

Abstract: COVID-19 patients frequently exhibit coagulation abnormalities and thrombotic events. In this meta-analysis, we investigated the association between coagulopathy and the severity of COVID-19 illness. Using PubMed, Embase, Cochrane, WanFang Database, CNKI, and medRxiv, a systematic literature search was conducted for studies published between December 1, 2019 and May 1, 2020. We then analyzed coagulation parameters in COVID-19 patients exhibiting less severe and more severe symptoms. All statistical analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 40 publications
1
33
0
1
Order By: Relevance
“…These results showed that the model has a good predictive ability, and the predictive ability of the model was higher than that of individual genes. Previous studies have shown that C‐reactive protein, ferritin, fibrinogen, d ‐dimer, lactate, and procalcitonin are common clinical indicators associated with SARS‐CoV‐2 infection and severity, which can assist in the diagnosis and treatment of COVID‐19 22–25 . The diagnostic ability of our model is also higher than these clinical indicators in the same data set.…”
Section: Discussionmentioning
confidence: 72%
“…These results showed that the model has a good predictive ability, and the predictive ability of the model was higher than that of individual genes. Previous studies have shown that C‐reactive protein, ferritin, fibrinogen, d ‐dimer, lactate, and procalcitonin are common clinical indicators associated with SARS‐CoV‐2 infection and severity, which can assist in the diagnosis and treatment of COVID‐19 22–25 . The diagnostic ability of our model is also higher than these clinical indicators in the same data set.…”
Section: Discussionmentioning
confidence: 72%
“…Pooled mortality among patients with vs. without thromboembolic events was 23% (95% CI: 14%–32%) vs. 13% (95% CI: 6%–22%) [ 71 ]. Although the exact underlying pathophysiology that leads to COVID-19-associated coagulopathy is not fully understood, it appears that endotheliopathy, vasoocclusion/stasis, and inflammation-associated activation of coagulation contribute to the respective complications [ [72] , [73] , [74] ].…”
Section: Pathophysiology Of Cardsmentioning
confidence: 99%
“…The second form of systemic pathology is hypercoagulation, resulting in microthrombus formation and, somewhat counterintuitively, bleeding (Al-Samkari et al, 2020; Bryce et al, 2020). While sharing features with the more commonly known disseminated intravascular coagulation (DIC), COVID-induced hypercoagulability exhibits unique aspects including preserved levels of circulating fibrinogen and massively increased levels of von Willebrand factor from activated or damaged endothelial cells (Ward et al, 2020; Zhang et al, 2020). The clinical ramifications are that COVID-19 patients have a dramatically increased risk of stroke, myocardial infarction, pulmonary and deep venous thromboembolism, and major hemorrhage (Helms et al, 2020b; Castro and Frishman, 2021).…”
Section: A Brief Overview Of Covid-19mentioning
confidence: 99%